Activated Microglia Mediate the Motor Neuron‐, Synaptic Denervation‐ and Muscle Wasting‐Changes in Burn Injured Mice - Jingyuan Chen; Yoshinori Kitagawa; Fei Xie; Haobo Li; William R. Kem; Zerong You; Shingo Yasuhara; J. A. Jeevendra Martyn (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Muscle wasting (MW) of burn injury (BI) remains unresolved. Microglia‐mediated inflammatory cytokine/chemokine release, motor neuron loss (MNL) and MW is observed after BI but connection of the central changes to synaptic‐denervation and MW is unelucidated. Stimulation of microglia α7acetylcholine receptors (α7AChRs), a Chrna7gene‐product, exhibits anti‐inflammatory properties (decreased cytokine/chemokines). Hypothesis tested was that exploitation of the microglia α7AChR anti‐inflammatory properties mitigates cytokine inflammatory responses, MNL, synaptic‐denervation and MW of BI. Methods Wild‐type or α7AChR knockout (A7KO) mice received 30% body BI or Sham BI (SB) under anaesthesia with and without selective α7AChR agonist, GTS‐21. Lumbar spinal cord tissue and hindlimb muscles were harvested. Immunohistochemistry, TUNEL assay for apoptosis and/or Nissl staining were used to examine microglia (Iba1 staining), MNL (NeuN staining) and synapse morphology (synaptophysin for nerve and α‐bungarotoxin for muscle α7AChR). Spinal cytokine/chemokine transcripts, inflammatory transducer‐protein expression and tibialis, soleus and gastrocnemius muscle weights were measured. Results BI to Wild‐type mice caused significant microgliosis (5.8‐fold increase, p < 0.001) and upregulated TNF‐α, IL‐1β, CXCL2, MCP‐1 transcripts, and inflammatory transducer‐protein (STAT3 and NF‐κB, p < 0.01) expression together with increased transcripts of iNOS (p < 0.01) and CD86 (p < 0.01) at day 14 reflective of inflammatory M1 microglia phenotype. Significant apoptosis, MNL (32.2% reduction, p < 0.05), increased spinal caspase‐3 expression (> 1100‐fold, p < 0.05) and synaptic denervation were observed with BI. The tibialis muscle endplates (synapse) of SB had a smooth pretzel shaped appearance with good apposition of presynaptic nerve to postsynaptic muscle. In BI mice, the normal pretzel‐like appearance was lost, and the endplates were fragmented with less nerve to muscle apposition. Tibialis, soleus, and gastrocnemius mass were decreased 31.7% (p < 0.01), 23.4% (p < 0.01) and 27.5% (p < 0.01) relative to SB. The A7KO mice with SB showed significant MNL loss (61.5% reduction, p < 0.05), which was aggravated with BI, accompanied by significantly higher expression of STAT3 and Nf‐kB (p < 0.05). GTS‐21 ameliorated the spinal expression of above enumerated cytokines/chemokines, inflammatory transducer‐proteins (p < 0.05) together with mitigated MNL (p < 0.05), synaptic denervation (p < 0.05) and decreased MW of tibialis (25%), gastrocnemius (15%) and soleus (20%) relative to untreated wild type BI mice (p < 0.01). GTS‐21 beneficial effects were absent in the A7KO mice. Conclusions Microglia‐mediated inflammatory responses play pivotal role in MNL as decrease of inflammatory responses improved MNL; α7AChR stimulation also mitigated synaptic denervation and MW changes of BI. α7AChRs have a role in spinal homeostasis even in uninjured state.